Applying an adaptive method of the orthogonal Laguerre filtration of noise interference to increase the signal/noise ratio - Kozlovskyi, Valerii; Scherbak, Leonid; Martyniuk, Hanna; Zharovskyi, Ruslan; Balanyuk, Yuriy; Boiko, Yuliia (Eastern-European Journal of Enterprise Technologies, 2020)
A relevant task for control systems is to reduce the impact of noise interference in order to increase the signal/noise ratio (SNR). This issue is relevant to other technical systems as well. This work addresses the orthogonal Laguerre filtration of noise processes, which are described by the linear random processes. The proposed method of filtration makes it possible to reduce the influence of noise interference, which is described by the stationary linear random processes, in the operation of correlation systems. The essence of this method implies the use of orthogonal Laguerre filters as the input links of the correlation system. The sequence of the noise processes, which are uncorrelated over a significant time interval of their mutual shift, has been derived on the basis of orthogonal Laguerre filtration of the stationary white noise. Such processes are described by the stationary linear random processes and are the models of a wide range of noise interference, which are explored in the operation of various technical systems, including control, detection, recognition, measurement systems, etc. The application of this method decreases the effect of noise interference with different correlation-spectral characteristics and increases the SNR at the output from the correlation system. Practical tasks on reducing the action of stationary noise interference have been solved within the framework of the proposed adaptive method of orthogonal Laguerre filtration; to this end, the article shows a structural-logical scheme of the correlation system. Using the software, the algorithm of the adaptive filtration based on the complex Laguerre filters has been implemented. The implementation has been carried out for an actual noise interference that belongs to the RLC class of noise, employing the pre-training of the filter. The effectiveness of reducing the impact of the predefined stationary noise interference has been confirmed by the derived efficiency coefficients the size of –6 dB and –16 dB for the set of the interference zeroing points